Angelicin Alleviates Post-Trauma Osteoarthritis Progression by Regulating Macrophage Polarization via STAT3 Signaling Pathway - Tian, Zhansong; Zeng, Fanchun; Zhao, Chunrong; Dong, Shiwu (Frontiers in Pharmacology, 2021)
Post-trauma osteoarthritis (PTOA) is the most common articular disease characterized by degeneration and destruction of articular cartilage. Inflammatory response of local joint tissue induced by trauma is the most critical factor accelerating osteoarthritis (OA) progression. M1/M2 macrophages polarization and repolarization participated in local inflammation, which plays a major role in the progression of OA. Regulating effect of macrophage polarization has been reported as a potential therapy to alleviate OA progression. Synovitis induced by polarized macrophages could profoundly affect the chondrocyte and cartilage matrix. Generally, anti-inflammatory medications widely used in clinical practice have serious side effects. Therefore, we focus on exploring a new therapeutic strategy with fewer side effects to alleviate the synovitis. Angelicin (ANG) is traditional medicine in various folk medicine. Previous studies has revealed that angelicin have an inhibitory effect on inflammation, tumor growth, DNA damage, and virus proliferation. But its specific effects on influencing the process of OA were barely reported. In this study, the molecular mechanism of angelicin in vivo and in vitro was clearly investigated. Results showed that angelicin could regulate the M1/M2 ratio and function and alleviate the development of PTOA in the meanwhile. Bone marrow monocytes (BMMs) were isolated and induced by macrophage colony-stimulating factor (M-CSF), lipopolysaccharide (LPS) and interferon (IFN)-γ for M1 polarization and interleukin (IL)-4/IL-13 for M2 polarization. Subsequently, repolarization intervention were performed. The results suggest that angelicin can repolarize M1 towards M2 macrophages upregulating the expression of CD9. Besides, angelicin can also protect and maintain M2 polarization in the presence of LPS/IFN-γ, subsequently downregulate the expression of inflammatory mediators such as IL-1β and TNF-α. Mechanistically, angelicin can activate the p-STAT3/STAT3 pathway by conducting CD9/gp130 to repolarize towards M2 macrophages. These results suggest angelicin can alleviate the progression of OA by regulating M1/M2 polarization via the STAT3/p-STAT3 pathway. Therefore, angelicin has shown its effective therapeutic value in OA clinical treatment.